2022
DOI: 10.15244/pjoes/152381
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols Content, Chelating Properties and Adsorption Isotherms and Kinetics of Red and Yellow Pomegranate Peels (<i>Punica granatum</i> L.) Towards Lead (II)

Abstract: Metal pollutants produced by industrial wastewaters have become a global concern given their impact on the environment and human health. The purpose of this study was to assess the polyphenols content and the iron chelating activity in the peels of two pomegranate varieties. After the biomass characterization via FT-IR, point of zero charge and surface functional groups analysis, the lead adsorption was then investigated by batch method. Finally, the regeneration of the biomasses was performed by acidic desorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Tis measurement provides evidence on considerable quantities of phenolic compounds in the pomegranate peel that have two major components, carbon and oxygen, in their structure. Te TPC of the two types of pomegranate peel was reported to be 102.9 ± 0.9 and 85.9 ± 1.3 mg GAE/g DW [31]. Several studies have found pomegranate peel to be rich in phenolic compounds [32][33][34][35][36][37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tis measurement provides evidence on considerable quantities of phenolic compounds in the pomegranate peel that have two major components, carbon and oxygen, in their structure. Te TPC of the two types of pomegranate peel was reported to be 102.9 ± 0.9 and 85.9 ± 1.3 mg GAE/g DW [31]. Several studies have found pomegranate peel to be rich in phenolic compounds [32][33][34][35][36][37].…”
Section: Resultsmentioning
confidence: 99%
“…Te peaks in the narrow area of 1390−1310 cm −1 are associated with O-H phenolic bending. Te peaks at 1232 and 1033 cm −1 display the stretching vibrations of the carbonyl group (C-O) [3,4,31]. Tese data confrm that the pomegranate peel is rich in phenolic compounds which have carbon and oxygen as their two main elements.…”
Section: Ftir Analysismentioning
confidence: 90%
“…1 shows the FT-IR spectra of (a) tannin-rich pomegranate peel powder and (b) PT-ED. The wide peaks at 3600-3100 cm −1 show the stretching vibration of the O─H group of phenolic [ [27] , [28] , [29] , [30] , [31] , [32] ]. The C─C bond of the ring was displayed at the wavelength 1446 cm −1 [ 12 ].…”
Section: Resultsmentioning
confidence: 99%